Analisis Perbandingan Faktor-Faktor Yang Memengaruhi Perilaku Konsumen Dalam Membeli Helm Merek KYT, MDS, INK, GM (Studi Kasus: Mahasiswa STIEAD dan Mahasiswa UMJ) - Koesmawan Koesmawan; Darwin Erhandy; Dede` Dahlan (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2019)
This research is a quantitative research using the Analytical Hierarchy Process (AHP) technique, conducted in two Muhammadiyah universities located in Jakarta. This study uses a sample of 60 respondents, consisting of 30 respondents from STIEAD Jakarta students and 30 UMJ student respondents. This study aims to determine which factors influence the purchase of this helmet through consumer behavior theory so that in the future, the helmet maker can determine what elements should be properly presented in the manufacture of helmets. As for the development of science, this research wants to know or expand the insight into the use of the AHP concept in various situations, especially in the scope of the consumer behavior concept. The results of this study conclude that the variables that influence STIEAD students in the purchase of helmets simultaneously are the promotion variable with a score of 0.4588, followed by the price variable with a score of 0.1484, the product quality variable score of 0.1349, the design/score score of 0,1363, and Prestige Resell score of 0.1216. While for UMJ students, the promotion variable with a score of 0.4902 was very influential for UMJ students in choosing a helmet. A score of 0.0918 follows the resell & prestige variable, the price score is 0.1513, the design/taste score is 0.1362, and the product quality score is 0.1304. And in combination, STIEAD and UMJ students are promotion variables with a score of 0.4971, which is very influential for STIEAD and UMJ students in choosing a helmet. The price variable followed with a score of 0.1482, a Design Price score of 0.1342, Product Quality score of 0.1283, and Prestige & Resell score of 0.0922.